German economy still running at high capacity - Ferdinand Fichtner; Karl Brenke; Marius Clemens; Simon Junker; Claus Michelsen; Thore Schlaak (DIW Economic Bulletin, 2017)
The German economy is on track for continued growth. Due to the unexpectedly robust first six months of 2017, the German Institute for Economic Research is raising its forecast for GDP growth to 1.9 percent for the current year. This year and arguably for the coming two years, the country's output will exceed potential output; nonetheless, there is no risk of overheating. Economic growth will slow down somewhat, not only because demand from abroad will be expanding at a slower rate. Additionally, both private consumer and public spending will experience only moderate increases, while companies will continue their reluctance to invest in new machines and facilities. Inflation should rise only slightly, even givenmodest wage increases, which further reflects the continued growth of the potential labor pool. The economy is also beset with numerous risks. For example, exports could be adversely affected if the external value of the euro were to rise - for instance as a result of a more restrictive monetary policy than assumed here. And it is entirely possible that increasing protectionism could hinder world trade.
Keywords: E32; E66; F01; 330; business cycle forecast; economic outlook